Qualitative effects of the addition of withered grapes to a freshly produced red wine: the traditional governo all'uso toscano practice. (29th April 2020) - Guerrini, L.; Calamai, L.; Angeloni, G.; Masella, P.; Parenti, A.
Abstract: Background and Aims: Governo all'uso toscano (GUT) is a traditional winemaking practice where withered grapes are added to a freshly fermented wine. This results in a second alcoholic fermentation and a distinctive wine, in which there is renewed interest. Grape withering is problematic for winemakers, however, both in terms of cost and risks. It is therefore important to determine the minimum amount of withered grapes needed to typify the wine in order to minimise risks and costs. Methods and Results: During the trials, Sangiovese grapes were withered for 2 months in a dedicated room, a 'fruttaio', with a resulting mass loss of about 40%. Afterwards, withered grapes (5–20% berry mass/wine mass) were added to a Control wine to reproduce the GUT procedure. The GUT technique significantly changed the chemical profile of the wines. Ethanol, colour intensity and hue increased, while acidity decreased. Malolactic fermentation occurred simultaneously with the second alcoholic fermentation in all GUT wines, but not in the Control wines. The GUT practice significantly changed the volatile profile, including the concentration of several primary grape compounds, such as aromatic alcohols, C6 compounds and terpenoids, and of several fermentation compounds. Conclusion: Under the experimental conditions, the optimal amount of withered grapes added to the base wine was 5%. Significance of the Study: The study described the oenological effects of GUT and the optimisation of the amount of withered grapes required to make a wine with this characteristic winemaking practice clearly recognisable.